Research on the Integration Pathway of “Position-Course-Competition-Certification“ for the Converged Media Technology and Operations Major within the Framework of Industry-Education Integration - Liu Rong; WuLiSha (Journal of Exploration of Vocational Education, 2026)
Against the backdrop of deepening media convergence, the demand for high-quality, versatile, and technically skilled professionals in integrated media is growing increasingly urgent. This places higher demands on the quality of talent supply in vocational education. However, at present, there remains a gap between the supply side and demand side in talent cultivation for the Integrated Media Technology and Operations major in higher vocational colleges. This gap is manifested in the misalignment between training objectives and industry needs, the dislocation between curriculum design and job competency requirements, and the separation of practical teaching from real-world work scenarios. Taking the integrated talent cultivation model of "Post-Course-Competition-Certification" as the theoretical basis, this paper provides an in-depth analysis of multiple dimensions, including the competency spectrum of "Post," the systematic reconstruction of "Course," the guiding and catalytic role of "Competition," and the evaluative feedback of "Certification." It aims to offer a theoretical foundation for innovating the talent cultivation model in vocational education and effectively serving industrial development.